Columnar-to-equiaxed transitions in additively manufactured face-centered cubic multi-principal element alloys - Mengyao Zheng; Yu Liao; Zheng Zhou; Hao Zhang; Chuanwei Li; Zhong Long; Jianfeng Gu (Additive Manufacturing Letters)
Columnar-to-equiaxed transition (CET) represents a critical microstructural characteristic in additively manufactured alloys. Precise control over CET is essential for achieving high-performance metallic components through additive manufacturing. In this study, two face-centered cubic multi-principal element alloys (MPEAs), namely CoCrNi and FeCoCrNi, were fabricated via laser directed energy deposition. The influence of process parameter and alloy composition on the CET of the two MPEAs was investigated. The results demonstrated that pronounced CET phenomena were observed in both MPEAs as the laser power increased and the scanning speed decreased. However, significant variations were noted in their CET parameters, equiaxed grain fraction, and crystallographic texture. Subsequently, the impact of process parameters on temperature gradient, solidification rate, and molten pool morphology was investigated via finite element modelling, revealing the formation mechanisms of the grain morphology and texture in additively manufactured CoCrNi and FeCoCrNi alloys. Additionally, the results of thermodynamic calculation revealed significant differences in the growth restriction factors between the two MPEAs, thereby explaining the distinct CET behaviors observed in the two MPEAs.